Legislative Amendment of Citizen Initiatives: Where the “Will of the Voter” Meets the “Consent of the Elector” - Langhauser, Derek (Maine Policy Review, 2021)
This article discusses the issues involved in legislative amendment of citizen initiatives in Maine by explaining the legislature’s authority to amend or repeal citizen initiatives, how and why the Maine Constitution specifically provides for that authority, and how and why that approach is conceptually consistent with numerous other provisions and principles of our Constitution. This article further suggests the types of issues that, regardless of the subject matter in question, the legislature should consider in determining whether, and if so how and when, to change a directly democratic act of the people. Such considerations when earnestly applied can serve to balance the legislature’s representational duty to mind the popular will as well as its leadership responsibility to steward the state with the additional exercise of the legislature’s own lawmaking power.